Impact of natural resource rents and economic growth on environmental degradation in the context of COP-26: Evidence from low-income, middle-income, and high-income Asian countries. (January 2023) - Luo, Jing; Ali, Syed Ahtsham; Aziz, Babar; Aljarba, Ahmed; Akeel, Hatem; Hanif, Imran
Abstract: This study investigates the influence of natural resource rents and economic growth on environmental degradation by using the three classifications of the Asian countries based on per capita income. A panel data from 1990 to 2018 is analyzed to determine the cointegration relationship through Mean Group (MG) regression. The calculations indicate that there is a strong positive correlation between natural resource rents and carbon emissions, particularly in the group of low-income countries. The results indicate a positive correlation between economic growth and carbon emissions for the middle and low-income groups while there is a negative relationship found in the group of high-income countries. The study suggests that to achieve the targets of COP-26, joint efforts of high, middle, and low-income countries are required on urgent basis to reduce carbon emissions. The group of high-income countries is required to improve the resource rents policies such as the search for alternative renewable sources, plantation of trees on a large scale, judicious way of energy preservation, and use of biofuels at the household level. The group of middle and low-income countries needs to adopt environment-friendly economic growth along with the aforementioned policies to preserve natural resources. Highlights: In Asia, natural resource consumption is a hurdle to achieve COP26 targets. In low, middle and high income countries population growth is restricting to achieve COP26 targets. Economic growth in low and middle-income countries is stimulating CO2 emissions. Natural resources consumption is helping to mitigate CO2 emissions in Oil exporting countries. Technological advancement is necessary to mitigate CO2 emissions and to achieve COP26 goals.